2021
DOI: 10.5057/ijae.ijae-d-20-00011
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Office Worker’s Emotion Types Using Two-dimensional Model Consisted of Biometric Signals

Abstract: A model that estimates emotion types from bio-signals obtained by wearable monitoring systems was developed. A total of 470 events of strongly conscious emotions (happy, relaxed, sad, and angry) during work hours were recorded in 11 office workers under a total of 911 days of continuous monitoring of pulse rate, pulse rate variability (PRV), skin temperature, body motion, and conversation time with a bracelet-shape wearable sensor. When the four emotion types were developed on the two-dimensional plane consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Notably, strong emotional events were less frequently collected through voluntary responses that were not triggered by smartphone notifications. In a previous study that collected strong emotional experiences ( 42 ), a total of 954 experiences from 911 days × 11 subjects were collected, suggesting that strong emotions can be collected at a rate of 0.095 [times/days × people]. Compared to this rate, our rate of 0.038 (=9 [times] over 14 [days] × 17 [participants]) [times/days × people] was not extremely low.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Notably, strong emotional events were less frequently collected through voluntary responses that were not triggered by smartphone notifications. In a previous study that collected strong emotional experiences ( 42 ), a total of 954 experiences from 911 days × 11 subjects were collected, suggesting that strong emotions can be collected at a rate of 0.095 [times/days × people]. Compared to this rate, our rate of 0.038 (=9 [times] over 14 [days] × 17 [participants]) [times/days × people] was not extremely low.…”
Section: Discussionmentioning
confidence: 76%
“…This biased demographic characteristic may limit the generalizability of our findings to the broader population of remote workers. Regarding this limitation, our sample size was relatively small compared with previous studies, although similar sample sizes were sometimes reported in pilot studies ( 16 , 19 , 42 , 68 , 69 ). To enhance the generalizability of our findings, future studies future studies should aim for larger sample sizes that encompass diverse participants.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations